Personality and universal design for learning in management education - Douglas Sanford Jr.; Filiz Tabak (Organization Management Journal (OMJ), 2023)
Purpose - This paper aims to improve the understanding of student readiness for universal design for learning (UDL), thereby reducing a barrier to its adoption by management faculty. It explores how students' personality (conscientiousness and openness to experience) affects their readiness to embrace UDL and investigate how that relationship is mediated by self-directed learning (SDL). Design/methodology/approach - Analysis uses survey data from students in management courses. From these data are created multi-item constructs and control variables. A mediated regression model that uses bootstrapping to estimate parameters and standard errors generates the results. Findings - The findings were that SDL is strongly related to student readiness for UDL and that SDL fully mediates the relationship between conscientiousness and UDL. Openness to experience, however, directly relates to UDL without any mediation. Research limitations/implications - This research applies only to one institution and two management courses. The methodology used in this study is limited to one part of the UDL model, which is a measure of student readiness to engage in choice. Future research can extend this model to other courses and institutions and other parts of the UDL model. Practical implications - These findings provide insight into the student characteristics that enable them to gain empowerment and motivation from the UDL approach. Implementation of UDL in management education may require learning management strategies that accommodate student readiness for UDL. This study makes progress in identifying student characteristics that explain this readiness. Social implications - UDL can improve management education by making it more accessible to students with different personalities and learning styles. Originality/value - This study developed a method for analyzing the applicability of UDL in management education. It also devised and implemented a new survey measure for student readiness for UDL.
Keywords: 650; Conscientiousness; Management education; Openness to experience; Self-directed learning; Universal design for learning